2008
DOI: 10.1073/pnas.0804437105
|View full text |Cite
|
Sign up to set email alerts
|

Functional and comparative metagenomic analysis of bile salt hydrolase activity in the human gut microbiome

Abstract: Bile salt hydrolases (BSHs) catalyze the ''gateway'' reaction in a wider pathway of bile acid modification by the gut microbiota. Because bile acids function as signaling molecules regulating their own biosynthesis, lipid absorption, cholesterol homeostasis, and local mucosal defenses in the intestine, microbial BSH activity has the potential to greatly influence host physiology. However, the function, distribution, and abundance of BSH enzymes in the gut community are unknown. Here, we show that BSH activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
728
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 870 publications
(788 citation statements)
references
References 37 publications
25
728
0
3
Order By: Relevance
“…They also proposed the term 'metabolic endotoxemia' to describe the chronic low-grade systemic inflammation characteristic of obesity and type 2 diabetes (16) . Improved gut barrier activity resulted from prebiotic induction of the gut hormone glucagon-like peptide-2, a result confirmed in a later animal experiment (78) . More recently, Everard et al (155) confirmed Cani's earlier work that the prebiotic oligofructose could reduce gut permeability and associated metabolic endotoxemia and obesity in high-fat-fed animals through induction of intestinal endocannabinoids.…”
Section: Reducing Cvd Risk With Prebioticsmentioning
confidence: 63%
See 1 more Smart Citation
“…They also proposed the term 'metabolic endotoxemia' to describe the chronic low-grade systemic inflammation characteristic of obesity and type 2 diabetes (16) . Improved gut barrier activity resulted from prebiotic induction of the gut hormone glucagon-like peptide-2, a result confirmed in a later animal experiment (78) . More recently, Everard et al (155) confirmed Cani's earlier work that the prebiotic oligofructose could reduce gut permeability and associated metabolic endotoxemia and obesity in high-fat-fed animals through induction of intestinal endocannabinoids.…”
Section: Reducing Cvd Risk With Prebioticsmentioning
confidence: 63%
“…Similarly, SCFA have been shown to regulate adipocyte hormone production, not least of leptin (75) , the obesity hormone, and to control inflammatory processes in adipose tissue (76) , processes intimately involved in CVD risk, and possibly also impact on the way energy is stored or burnt in the body controlling adiposity and thermogenesis (15,77) . Microbial deconjugation of BA and the enterohepatic circulation of BA is a core activity of the human gut microbiota and is thought to directly regulate cholesterol levels in the blood (78,79) . Conjugated BA are secreted into the small intestine to aid micelle formation and fat absorption.…”
Section: An Anthropology Of Diet: Microbe Interactions Within the Hummentioning
confidence: 99%
“…Thus, these data may also provide hints to possible energy storage mechanisms in lowland gorillas, similar to those taking place in humans under high-caloric diets (Jones et al, 2008;Martin et al, 2007). Furthermore, fat deposition and storage are important evolutionary discriminant features between humans and non-human primates (Horrobin, 1999;Navarrete et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…7,8,11 Follow-up studies confirmed that germ-free animals have elevated conjugated bile acids throughout the intestine with no deconjugation and strongly decreased fecal excretion. 9 It has been hypothesized that increases in deconjugated bile acids may result in reduced farnesoid X receptor activation, increased cholesterol catabolism, reduced inhibition of liver X receptor (LXR) and upregulation of adenosine triphosphate-binding cassette (ABC)G5/G8 transporters. These transporters efflux cholesterol from hepatocytes and enterocytes 18 and are stimulated in the presence of deconjugated bile acids.…”
Section: Weekmentioning
confidence: 99%
“…8 This was substantiated by showing that germ-free animals have elevated levels of conjugated bile acids throughout the intestine, significantly reduced fecal biliary excretion and three times the bile-acid concentration in bile. [9][10][11] Further, it was shown that mice treated with oral antibiotics for 3 days increased biliary bile-acid output threefold, whereas fecal output decreased by 70%. 12 In addition, porcine studies have demonstrated that increasing the bile salt hydrolase (BSH) activity of the intestinal microflora results in a significant increase in the deconjugated bile-acid pool 13 and a reduction in circulating cholesterol.…”
Section: Introductionmentioning
confidence: 99%